Progress of research on adverse events in intrahospital transport of critically ill patients (急诊危重症患者院内转运不良事件研究进展) - GAO Wei (高伟); PEI Xiaolu (裴晓璐); WANG Guiqian (王桂倩); GUO Bingjie (郭冰洁); AN Ran (安然); WANG Shuang (王爽) (Journal of International Translational Medicine Limited, 2023)
Department of Emergency Medicine is an important division providing medical care to critically ill patients. Transport of critically ill patients is often required from the intensive care unit (ICU) to other hospital departments for imaging or medical procedures. Changes in treatment environment, insufficient medical resources during transport may lead to adverse events. There is an urgent need to reduce the risk of adverse events during transport. This paper summarized reviews studies on adverse events in perspectives of current situation, risk factors and nursing countermeasures, and provided reference for quality improvement of intrahospital transport of critically ill patients. (急诊科是急危重症患者诊疗的重要平台。在急诊科护理工作中, 危重症患者常因检查或治疗的需要进行院内转运, 转运过程虽短, 但由于治疗环境的改变, 转运过程中治疗、护理资源的缺乏, 可能导致不良事件的发生。如何有效减少急诊危重症患者院内转运过程不良事件发生是临床急需解决的难题。本文对急诊危重症患者院内转运过程中不良事件的发生情况、风险因素分析以及护理干预策略进行综述, 旨在提高急诊危重症患者院内转运质量。)